Unraveling innovative treatments for spinal muscular atrophy: a brief review - Naseem, Sadia; Fatima, Shireen; Vijaya, D. Navya Sai (International Journal Of Community Medicine And Public Health, 2024)
In the past few years, there have been amazing breakthroughs in treating spinal muscular atrophy (SMA), which is a big deal considering it’s been studied for over a hundred years. Now, there are three approved therapies that all work to increase SMN protein production. They do this by fixing the genetic problem either by replacing the faulty SMN1 gene or by helping the SMN2 gene produce more of the right kind of protein. One way they do this is by using a special virus called adeno- associated viral vectors (AAV9) to deliver the gene therapy because the SMN1 gene is small enough to fit inside. The paper discusses the evolution of SMA treatment, focusing on advancements like gene therapy and new drug treatments. It highlights challenges in interpreting efficacy, especially regarding disease classification. Despite successes, issues like limited trial populations and varying disease stages pose complexities in care. With expanding treatment options, including those in advanced development stages, the landscape of SMA management grows more intricate. However, the importance of timely diagnosis and interdisciplinary clinical management remains crucial, recognizing that despite drug treatments, many patients still face significant disease burdens. This article aims to give a quick rundown of spinal muscular atrophy, starting from when people first noticed the disease up until now, when there are some really cool new treatments that are changing how the disease affects people.